Communication Challenges Of Culture And Stigma In The Control Of Cervical Cancer Among Rural Women In Kenya. - Kutto, Victoria Chepkemoi; Mulwo, Abraham Kiprop (Advances in Social Sciences Research Journal, 2015)
The paper is part of the literature review of an ongoing doctorate research on communication challenges in the control of cervical cancer among rural women in Kenya. The paper looks at communication challenges arising from culture and stigma, which contribute to setbacks in the control of cervical cancer among rural women. Culture and stigma are discussed in this paper because they address some of the concerns of the research questions in the study. Cervical cancer is preventable and also treatable at early stages, but statistics from various credible sources worldwide indicate that it is one of the cancers that is high in morbidity rates especially in sub-Saharan Africa. This paper interrogates how culture and stigma pose communication challenges that prevent women from seeking the necessary healthcare in order to achieve the four components of cancer control which are: prevention, detection, treatment and palliative care. The paper uses a qualitative approach in its methodology because the main research takes an interpretivist –constructivist philosophical stance. Recommendations and conclusions made are hoped to contribute knowledge to the field of cervical cancer control especially in rural communities. Key words: cervical cancer, culture, stigma, communication, and qualitative research